2007
DOI: 10.1021/ie070299v
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in a Biodiesel Reactor Using Supercritical Methanol

Abstract: Recent experimental studies on noncatalytic transesterification have shown that high reaction rates, which justify the commercial application of this process, can be obtained if the operating conditions are above the critical pressure and temperature of methanol. Although it is generally agreed that temperatures of >550 K and high methanol/oil ratios are required to obtain high conversions and high reaction rates, there is disagreement in the literature regarding the operating pressure, the assumed phase condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 11 publications
5
73
1
10
Order By: Relevance
“…This process exhibits advantages over the alkaline catalysis method, as it is a simple noncatalytic process, avoiding the removal of catalyst from the product and reducing wastewater. Hegel [14,15] reported that methanol and oil forms a single phase in the supercritical state in a tubular reactor. Bertoldi et al [16] carried out production of fatty acid ethyl esters from soybean oil transesterifi cation in supercritical ethanol and carbon dioxide as a cosolvent in a tubular reactor.…”
Section: Biofuelsmentioning
confidence: 99%
“…This process exhibits advantages over the alkaline catalysis method, as it is a simple noncatalytic process, avoiding the removal of catalyst from the product and reducing wastewater. Hegel [14,15] reported that methanol and oil forms a single phase in the supercritical state in a tubular reactor. Bertoldi et al [16] carried out production of fatty acid ethyl esters from soybean oil transesterifi cation in supercritical ethanol and carbon dioxide as a cosolvent in a tubular reactor.…”
Section: Biofuelsmentioning
confidence: 99%
“…The phase behavior of soybean oil-methanol with propane as a co-solvent was reported first (Hegel et al, 2007), followed by that for soybean oilmethanol and soybean oil-ethanol with carbon dioxide as the co-solvent (Anitescu et al, 2008). The study of the phase behavior of supercritical transesterification, when performed in a high-pressure view cell, revealed that the liquid -liquid (LL) alcohol -triglycerides mixture transforms to a vapor -liquid -liquid (VLL) phase equilibrium.…”
Section: The Phase Behavior Of Reactants In Supercritical Transesterimentioning
confidence: 99%
“…Finally, the VL equilibrium merges to a one-phase supercritical at nearly the estimated critical point of mixture. The transition temperature of the VLL to VL equilibriums decreases with increasing methanol to oil molar ratios (Anitescu et al, 2008;Hegel et al, 2007). For example, the reaction mixture of soybean oil and methanol are partially miscible up to temperatures close to 350 ºC at a methanol to oil molar ratio of 24:1, while the two liquid phases of soybean oil and methanol become completely miscible at 180 ºC and 157 ºC with a methanol to oil molar ratio of 40:1 and 65:1, respectively.…”
Section: The Phase Behavior Of Reactants In Supercritical Transesterimentioning
confidence: 99%
See 2 more Smart Citations